2014
DOI: 10.1371/journal.pone.0113930
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Correlates of Koala Persistence in a Low-Density Population

Abstract: It is widely postulated that nutritional factors drive bottom-up, resource-based patterns in herbivore ecology and distribution. There is, however, much controversy over the roles of different plant constituents and how these influence individual herbivores and herbivore populations. The density of koala (Phascolarctos cinereus) populations varies widely and many attribute population trends to variation in the nutritional quality of the eucalypt leaves of their diet, but there is little evidence to support thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 92 publications
(126 reference statements)
2
21
0
Order By: Relevance
“…The DigN mapping method using this index were tested by linking previous koala tree use frequency with mapped DigN from a WV2 image of an independent landscape in the study area. Results indicated greater koala tree use for trees with higher estimated DigN, which is consistent with previous studies [8,41]. Therefore, it is possible to estimate and map the variation in eucalypt foliar DigN over large areas using WV3-or WV2-derived multispectral data and these estimates are meaningful for the evaluation of koala habitat suitability.…”
Section: Discussionsupporting
confidence: 89%
“…The DigN mapping method using this index were tested by linking previous koala tree use frequency with mapped DigN from a WV2 image of an independent landscape in the study area. Results indicated greater koala tree use for trees with higher estimated DigN, which is consistent with previous studies [8,41]. Therefore, it is possible to estimate and map the variation in eucalypt foliar DigN over large areas using WV3-or WV2-derived multispectral data and these estimates are meaningful for the evaluation of koala habitat suitability.…”
Section: Discussionsupporting
confidence: 89%
“…Under these conditions, it is probably hard, if not impossible, to identify factors that are actually limiting. Having enjoyed considerable time in forests with plentiful animals, it may be an unfortunate conclusion, but in order to find out what limits primates, researchers will likely need to turn their attention to regions where animals are naturally scarce [e.g., Stalenberg et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is the first time that variation in nutritional quality and the corresponding impact of an invasive herbivore has been quantified at a landscape scale. Australian studies have identified nutritional factors, such as total N, the ratio of nitrogen to phenols, plant secondary metabolites (PSMs) such as FPCs as well as AvailN, as important determinants of distribution and local abundance of arboreal marsupials in Australian forests [ 6 – 8 , 41 , 42 ]. Therefore, the seasonal and spatial distribution of foliar AvailN concentrations in a dominant diet species such as kamahi may be a major determinant of the likely impact of invasive possum populations in NZ, and conceivably in other systems.…”
Section: Discussionmentioning
confidence: 99%